Returns to Investment in Education : The Case of Turkey - Patrinos, Harry Anthony; Psacharopoulos, George; Tansel, Aysit (World Bank, Washington, DC, 2019)
This paper estimates private and social returns to investment in education in Turkey, using the 2017 Household Labor Force Survey and alternative methodologies. The analysis uses the 1997 education reform of increasing compulsory education by three years as an instrument. This results in a private rate of return on the order of 16 percent for higher education and a social return of 10 percent. Using the number of children younger than age 15 in the household as an exclusion restriction, the analysis finds that returns to education for females are higher than those for males. Contrary to many findings in other countries, private returns to those working in the public sector are higher than those in the private sector, and private returns to those who followed the vocational track in secondary education are higher than those in the general academic track. The paper discusses the policy implications of the findings.